The Revival of Industrial Unions in Canada: The Extension and Adaptation of Industrial Union Practices to the New Economy - Yates, Charlotte A. B. (Charlotte Alyce Bronwen) (Trade Unions in Renewal: A Comparative Study, 2003)
Analyzes how, in the late 1980s, industrial unions such as the Canadian Auto Workers adapted successfully to the growth of the service sector and the changing composition of the workforce. Concludes that problems of internal union structure and identity, as well as jurisdictional disputes between unions, are still not resolved.
Keywords: Canada; Industrial relations; Labor unions; United States